2014
DOI: 10.1136/bjsports-2013-093063
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, physiological and perceptual strain mediate alterations in match-play tennis under heat stress

Abstract: ObjectivesThis study compared the thermal, physiological and perceptual responses associated with match-play tennis in HOT (∼34°C wet-bulb-globe temperature (WBGT)) and COOL (∼19°C WBGT) conditions, along with the accompanying alterations in match characteristics.Methods12 male tennis players undertook two matches for an effective playing time (ie, ball in play) of 20 min, corresponding to ∼119 and ∼102 min of play in HOT and COOL conditions, respectively. Rectal and skin temperatures, heart rate, subjective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 36 publications
8
78
4
2
Order By: Relevance
“…Compared with other field studies, this is similar to the average peak core temperature reported in footballers playing at an ambient temperature of 43°C6 and tennis players in 37°C 7. Most (85%) of the cyclists participating in the study reached a core temperature of at least 39°C and 25% reached 40°C (figure 1).…”
Section: Discussionsupporting
confidence: 83%
“…Compared with other field studies, this is similar to the average peak core temperature reported in footballers playing at an ambient temperature of 43°C6 and tennis players in 37°C 7. Most (85%) of the cyclists participating in the study reached a core temperature of at least 39°C and 25% reached 40°C (figure 1).…”
Section: Discussionsupporting
confidence: 83%
“…Hornery et al (2007) support this theory despite converse relations between hard and clay courts and conclude that further physiological variables need to be considered, for example temperature. This assumption is in accordance with the findings of Périard et al (2014), who investigate the influence of heat on inter alia match play characteristics. The twelve participants of their study, male players of different performance levels, took on average a 9.6 second longer break between two points in hot conditions.…”
Section: Introductionsupporting
confidence: 91%
“…Although the mechanisms behind this were previously not suggested, this could be 5 plausible due to the associations between increases in body temperature and water retention mechanisms (Takamata et al 1995). Increases in body temperature has also been associated with perceptual triggers that may cause behavioural changes such as timing and extent of fluid intake to alleviate the anticipated thermoregulatory onslaught (Phillips et al 1984;Johnson et al 2010;Periard et al 2014). This is similar to that which has been seen between thermal discomfort and pacing strategies in the heat (Cheung 2010;Schlader et al 2011).…”
Section: Introductionsupporting
confidence: 61%